2018
DOI: 10.1111/ppa.12825
|View full text |Cite
|
Sign up to set email alerts
|

Cold plasma: a potential new method to manage postharvest diseases caused by fungal plant pathogens

Abstract: Development of alternative, chemical‐free approaches for control of postharvest fungi on a commercial scale has become a challenge for plant pathologists in recent years. Although there are several established techniques such as heat that are used as postharvest treatments, they often have disadvantages, including alteration of food quality due to physiological responses to the treatment, or environmental pollution. A promising new postharvest treatment is cold plasma, which is a gas‐derived mix of atoms, exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 106 publications
(143 reference statements)
2
23
0
Order By: Relevance
“…Indeed, the reduction in germination following longer exposure to CP indicated that the inhibition was permanent. Other studies have reported similar observations, with longer exposure times increasing the efficacy of treatment (discussed in Siddique et al, 2018a). More importantly, for growth rates it was found that a similar result could be achieved with the same treatment duration but from a greater distance, by conducting the treatment in a sealed environment.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Indeed, the reduction in germination following longer exposure to CP indicated that the inhibition was permanent. Other studies have reported similar observations, with longer exposure times increasing the efficacy of treatment (discussed in Siddique et al, 2018a). More importantly, for growth rates it was found that a similar result could be achieved with the same treatment duration but from a greater distance, by conducting the treatment in a sealed environment.…”
Section: Discussionsupporting
confidence: 63%
“…Cold plasma (CP) demonstrates strong potential for the control of fungi that cause postharvest diseases in fruit, vegetables, nuts and grains and may be a possible replacement for fungicides (Siddique et al , ). CP is produced by applying an electrical charge to a gas, which ionizes the gas to produce a mixture of excited molecules, charged particles, reactive oxygen and nitrogen species, and some UV light and ozone.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, SEM analysis demonstrated modifications of the external shape of conidia, which could be attributed to the decomposition of organic components by etching and photo-desorption associated with chemical bond breakage, and consequent formation of volatile compounds 65 . www.nature.com/scientificreports www.nature.com/scientificreports/ Until now, few studies have investigated LTP to control postharvest fungal diseases 5 . Indirect plasma treatments have been successfully applied to inactivate Aspergillus ochraceus, Penicillium expansum and P. digitatum 86,87 and other fungi and yeast contaminating fresh produce like fruits and vegetables 88 .…”
Section: Discussionmentioning
confidence: 99%
“…Innovative technologies, based on sustainability, human safety, and long-term eco-safety, has been recently promoted and investigated. Among those, the atmospheric pressure low temperature plasma (LTP) represents a novel promising tool 5 . LTPs can be produced with different discharge configurations, such as corona, micro-hollow cathode, gliding arc, atmospheric uniform glow, dielectric barrier discharges, plasma jet and needle [6][7][8][9][10][11][12][13][14] .…”
mentioning
confidence: 99%
“…(2020) 10:2667 | https://doi.org/10.1038/s41598-020-59097-x www.nature.com/scientificreports www.nature.com/scientificreports/ meristems and predisposing them for fast growth resumption, plasma may have also suppressed fungal growth thus allowing leaves to become larger. It is known that non-thermal plasma treatment reduces the fungal growth and up-regulates resistance genes in plants 40,41 .…”
Section: Discussionmentioning
confidence: 99%